Blockchain for Smart Grid Energy Trading: Opportunities and Cybersecurity Challenges - Iboro Akpan Essien; Geraldine Chika Nwokocha; Eseoghene Daniel Erigha; Ehimah Obuse; Ayorinde Olayiwola Akindemowo (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The integration of blockchain technology in smart grid energy trading has emerged as a transformative approach to enhance efficiency, transparency, and decentralization in modern power systems. As energy grids evolve to incorporate distributed energy resources (DERs) such as solar photovoltaics, wind turbines, and battery storage systems, there is a growing need for secure, automated, and peer-to-peer energy trading mechanisms. Blockchain, with its decentralized, immutable, and transparent ledger, presents significant opportunities in enabling secure transactions, reducing transaction costs, and improving market access for prosumers—individuals or entities that both produce and consume energy. This explores the dual dimensions of blockchain applications in smart grid energy trading: the opportunities it presents and the cybersecurity challenges it introduces. Key opportunities include enhanced peer-to-peer energy trading, real-time settlement of transactions, and improved grid flexibility through smart contracts. Additionally, blockchain can facilitate the integration of renewable energy sources and enable innovative pricing models that incentivize grid balancing and demand-side participation. However, the deployment of blockchain in energy systems also raises critical cybersecurity concerns. These include risks of consensus mechanism vulnerabilities, smart contract exploits, data privacy breaches, and scalability limitations that may expose the energy grid to malicious attacks or operational failures. Moreover, the immutable nature of blockchain complicates the reversal of erroneous or fraudulent transactions. This underscores the importance of adopting robust cybersecurity frameworks, secure consensus algorithms, and privacy-preserving techniques to mitigate these risks. It calls for interdisciplinary collaboration between energy utilities, blockchain developers, cybersecurity experts, and regulators to design resilient systems. Ultimately, while blockchain offers promising solutions for decentralizing and optimizing energy trading, its widespread adoption in smart grids hinges on effectively addressing cybersecurity risks to ensure safe, reliable, and equitable energy markets in the digital era.